The food balance dynamics of the poultry meat - Rodica Chetroiu (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 7th Edition of the International Symposium, November 2016, Bucharest, 2016)
The paper performs an analysis of the food balance evolution for poultry meat, taking into account the internal production, imports, exports, consumption levels for this food product. Thus, the food balance had a favourable evolution in the recent years, the market supply of poultry having as a source both domestic production and quantities from imports. The amount of poultry meat from domestic production performed generally positive from year to year, so that in 2015 was by 16.5% more meat than in 2010. Also, the imports registered a significant increase of 34.3% during 2010-2015, completing the market demand, but, at the same time, being a factor of competition for the producers in our country. The highest growth was noted in exports, which were 58.9% higher in 2015 compared to 2010, demonstrating that domestic production of poultry meat has become more competitive in the international market, which managed to enter through increase technological performance and product quality. The result of these evolutions is the increased supply of poultry on the Romanian market, leading, in 2015, to find on the market an amount of 14.5% higher compared to 2010. At the same time, the meat poultry consumption increased, reaching in 2015, at 22.7 kg / capita, 24.7% higher compared to 2010.
Keywords: Q11; Q18; 330; meat; poultry; balance; production; import